Stick or leave – Pushing methanogens to biofilm formation for ex situ biomethanation. (November 2019) - Jensen, Mads Borgbjerg; Strübing, Dietmar; de Jonge, Nadieh; Nielsen, Jeppe Lund; Ottosen, Lars Ditlev Mørck; Koch, Konrad; Kofoed, Michael Vedel Wegener
Graphical abstract: Highlights: Substantial enhancement of methanogenic biofilm activity at short HRT. Planktonic hydrogenotrophic methanogens restricted biofilm growth at long HRT. Acetate accumulation at short HRT due to increased homoacetogenesis. Selected hydrogenotrophic biofilm species independent of HRT and sludge source. Abstract: Biomethanation exploits the ability of methanogenic archaea to convert CO2 and renewable H2 from electrolysis to biomethane. Biofilm reactors are promising for biomethanation scale-up due to high CH4 productivity and low energy input for H2 gas-liquid mass transfer. Effects of operational conditions on biofilm dynamics remain largely uncharacterized but may increase reactor potentials further. This study investigated the effect of hydraulic retention time (HRT) on methanogenic biofilm activity and composition. Commercial carriers floating in liquid were exposed to H2 /CO2 for 87 days with the liquid phase being subject to either 18 hours, 10 days, or 20 days HRT. Methanogenic biofilms were dominated by hydrogenotrophic methanogens, but biofilm CH4 productivity was enhanced at 18 hours HRT due to wash-out of competing planktonic species, which otherwise hampered proliferation of biofilm biomass at long HRT. It is suggested that high-rate biofilm reactors can increase methanogenic biofilm activity by minimizing the liquid's H2 exposure.